Generation of Bioelectricity Using Molasses as Fuel in Microbial Fuel Cells - Rojas-Flores, S. (2022)
The large amount of molasses that are generated in sugar-processing companies are not always redistributed for commercialization in by-products. Because of this, the present research uses these wastes as fuel in low-cost, lab-scale, single-chamber microbial fuel cells. Zinc and copper electrodes were used as electrodes and 100 mL of molasse in the chamber as fuel, managing to generate current and voltage peaks of 1.73 ± 0.13 mA and 0.953 ± 0.142 V. In monitoring the conductivity of the substrate, a maximum peak of 111.156 ± 8.45 mS/cm was observed, and a slightly acidic pH was observed throughout the monitoring. It was possible to obtain a power density of 5.45 ± 0.31 W/cm2 for a current density of 308.06 mA/cm2, while the yeast count showed a logarithmic curve throughout the monitoring. Finally, the molecular technique identified 100% of the special C. boidinii present in the anodic electrode. This research will give great benefits to sugar companies because they will be able to generate electricity using the molasses that cannot generate by-products.